Separation of Ownership and Control: Delegation as a Commitment Device - Aristotelis Boukouras (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
This paper provides a theoretical model for explaining the separation of ownership and control in firms. An entrepreneur hires a worker, whose effort is necessary for running a project. The workerś effort determines the probability that the project will be completed on time, but the worker receives some unobservable benefi t by continuing his employment in the project. Thus, motivating the worker requires an efficiency wage which is inflated by the private benefit. The entrepreneur would pay out a smaller wage if he could commit to terminate the project if a delay occurs, but this threat is not credible, because the project has positive continuation value. We show that hiring a manager can solve this time-inconsistency issue and reduce the efficiency wage. We extend the model to include managerial moral hazard and we examine the conditions under which separation of ownership and control is more likely to happen. The model is consistent with many of the findings of the empirical literature, while it generates some new predictions too.
Keywords: D86; G34; J31; L22; L26; 330; control structure; delegation; efficiency wage; entrepreneur; managerial contract; moral hazard; organizational hierarchy; private bene fits; separation of owner-ship and control; time-inconsistency